The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3126/ije.v9i1.27589
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Some Pollen Substitutes Diets on Caged Honey Bee Workers (Apis mellifera L.)

Abstract: Nutritional value of four proteinaceous diets and their physiological effects on honey bee workers were evaluated under laboratory conditions. The tested diets were as follows: diet 1 – date (Phoenix dactylifera L.) syrup, skimmed milk powder and dried brewer's yeast, diet 2 – Fenugreek (Trigonella foenum-graecum L.), Turmeric (Curcuma longa L.) powders and dried brewer's yeast, diet 3 – chickpea (Cicer arietinum L.) flour, wheat germ and dried brewer's yeast and diet 4 - soybean meal, skimmed milk powder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, in the present study, food intake was similar to field conditions, suggesting that the bees ingested sufficient food to maintain their physiological processes. The high food intake in the Z. mellis and S. cerevisiae diets coincided with vigorous food intake of S. cerevisiae-enriched diets reported in caged bees in another study (Amro, Younis & Ghania, 2020) and was similar to food intake in honey bee colonies under field conditions (Sihag & Gupta, 2011). High food intake of the two yeast-supplemented diets may be due to the nutritional components contained in yeast cells (e.g., lipids or proteins) (Herbert Jr & Shimanuki, 1978) and/or the volatiles produced by microbial metabolism (Christiaens et al, 2014).…”
Section: Food Intakesupporting
confidence: 80%
See 2 more Smart Citations
“…However, in the present study, food intake was similar to field conditions, suggesting that the bees ingested sufficient food to maintain their physiological processes. The high food intake in the Z. mellis and S. cerevisiae diets coincided with vigorous food intake of S. cerevisiae-enriched diets reported in caged bees in another study (Amro, Younis & Ghania, 2020) and was similar to food intake in honey bee colonies under field conditions (Sihag & Gupta, 2011). High food intake of the two yeast-supplemented diets may be due to the nutritional components contained in yeast cells (e.g., lipids or proteins) (Herbert Jr & Shimanuki, 1978) and/or the volatiles produced by microbial metabolism (Christiaens et al, 2014).…”
Section: Food Intakesupporting
confidence: 80%
“…Pioneering studies using caged bees found that using brewers' yeasts in bee food resulted in survival rates similar to those in bees fed pollen (Standifer et al, 1960). Recent studies have found that addition of brewers' yeasts to pollen substitutes can maintain bee longevity in cage conditions, resulting in survival rates similar to those observed in bees fed bee bread (Smodiš Škerl & Gregorc, 2014;Esanu, Radu-Rusu & Pop, 2018;Amro, Younis & Ghania, 2020). These studies and our results suggest that the nutrients provided by bee-associated yeasts are a good food source for bees and could further improve bee health.…”
Section: Survivalmentioning
confidence: 94%
See 1 more Smart Citation
“…In other studies, it is seen that different feeding patterns affect the lifespan. There are differences in incubator conditions (temperature/humidity) in some of the studies [ 12 , 13 , 55 , 56 ]. In a study that supports our findings, the difference between the groups according to the average lifespan was statistically significant in the trial which was formed in an incubator at 35 °C and 70% humidity with energy and protein-rich replacement feeds.…”
Section: Discussionmentioning
confidence: 99%
“…In the beekeeping sector, pollen and supplementary feeding with honey are used to prevent hunger and to develop a higher population in bee colonies in spring, by providing for brood formation in autumn and the beginning of winter in the young worker bee population, and in queen and drone breeding, in order to have healthier colonies and prevent loss of bees after using agricultural chemicals in plant production [ 8 , 9 , 10 ]. Especially, the composition and ratio of nutrients affect the longevity of honey bees [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%